Brazil in the World, the World in Brazil. Brasil no mundo, o mundo no Brasil Research Trends and Library Resources - González, Luis A. (Seminar on the Acquisition of Latin American Library Materials, 2017)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials